Who's the alien? Xenophobia in post-apartheid South Africa - Marguerite Duponchel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
In May 2008, South Africa became the theatre of widespread violent attacks against undesirable 'outsiders'. Over 60 were killed, hundreds wounded, and tens of thousands displaced. This analysis aims at identifying the characteristics of the victims in an attempt to portray the 'alien' using household data collected in February 2009 in the Johannesburg inner city and in Alexandra township. Results confirm that foreigners face a higher probability of being victimized on the ground of xenophobia. Relative poverty appears to have a positive impact on the probability of being attacked, especially in Alexandra township. Zimbabweans do also face a lower chance of victimization than other foreign nationals. Finally, the characteristics of the location, in particular high unemployment rate, influence the probability of attacks.
Keywords: O12; O55; 330; xenophobia; violence; South Africa